Film dissolution kinetics of aluminium at precisely adjusted pH‐values. Issue 6 (1st April 2016) - Walkner, Sarah; Hafner, Martina; Hassel, Achim Walter
Abstract : This work focuses on the corrosion of aluminium in alkaline solution particularly at pH 11.0. The pH value plays a key role in corrosion processes. In a certain pH range, either the metal dissolves or protective films may be formed. For performing electrochemical measurements at a precisely adjusted pH value a setup, the so called 'impedance titrator' is used, that allows adjusting and controlling of pH value very precisely, while characterising the film properties. Electrochemical impedance spectroscopy is performed to investigate the formation of corrosion products. By keeping the pH at a constant value and simultaneously offering the system a constant hydroxide concentration, film formation takes place under defined conditions and a full kinetic characterisation becomes possible. This special system is required as the behaviour of aluminium in alkaline solution is quite complex and a various number of competing reactions like oxide film formation and dissolution occur.